Developing a sustainable energy strategy for Midtjyllands Airport, Denmark. Issue 3 (1st March 2023) - Bujok, Patrick; Bjørn-Thygesen, Frans; Xydis, George
Abstract: The operation of airports is considered as particularly energy intensive and with the use of conventional energy sources, significant amounts of greenhouse gases (GHGs) are emitted, fueling the existential crisis of global warming. Hence, this study investigates the energy management system (EnMS) of Midtjyllands Airport with respect to its energy consumption, energy sources, and energy-related GHG emissions. The intention is to develop a sustainable energy strategy to close the gaps in their energy and carbon management by applying the methods of ISO 50001 EnMS and Airport Carbon Accreditation (ACA) Program. The findings reveal a total energy consumption of about 1 GWh including electricity (53%), natural gas (47%), and others (0.1%) while emitted GHGs account for in total 203 tCO2 e. With regard to the developed baseline trends, the designed objectives comprise (1) net zero GHG emissions without offsetting by 2030, (2) 40% reduction in energy consumption by 2025, and (3) 40% reduction of two energy performance indicators (EnPIs) by 2030. The achievement of the objectives is summarized in a nine-point action plan including the major actions of identifying significant energy users (SEUs), improving thermal state of total building envelope and heating system, as well as replacing the current electricity and natural gas contract with a renewable electricity and biogas contract, respectively.